Fibroblast‐derived exosomes promote epithelial cell proliferation through TGF‐β2 signalling pathway in severe asthma - Haj‐Salem, I.; Plante, S.; Gounni, A. S.; Rouabhia, M.; Chakir, J. (Allergy (Copenhagen), 2018)
Background Bronchial fibroblasts play a key role in airway remodelling in asthma. They regulate epithelial cell functions such as proliferation through growth factors, cytokines, chemokines and exosomes. The role of exosomes in the communication between epithelial cells and fibroblasts by vehiculing these mediators in asthma remains to be determined. Objective To evaluate the role of exosomes released by bronchial fibroblasts on epithelial cell proliferation in severe asthma. Methods Exosomes were obtained from culture media of primary bronchial fibroblasts and characterized using Western blot, electron microscopy and flow cytometry. Uptake profile of fluorescent‐labelled exosomes in epithelial cells was assessed by flow cytometry. Exosome cytokine content was analysed by Cytokine Arrays. Bronchial epithelial cell proliferation was evaluated by BrdU incorporation test. Exosome biogenesis/release was blocked using sphingomyelinase inhibitor. Plasmid transfection was used to modulate transforming growth factor beta 2 (TGF‐β2) gene expression. Results We showed that bronchial fibroblasts secreted exosomes, which were internalized by bronchial epithelial cells. Exosomes of severe asthmatic subjects' fibroblasts showed a lower level of TGF‐β2 and significantly increased the epithelial cell proliferation of both healthy and severe asthmatic subjects compared to healthy controls' exosomes. Overexpression of TGF‐β2 in severe asthmatics' fibroblasts induced enhanced TGF‐β2 in exosomes leading to a reduced proliferation of epithelial cells, whereas knockdown of TGF‐β2 enhanced epithelial cell proliferation. Conclusion Our study shows that exosomes are involved in fine‐tuning intercellular communication in asthma. Exosomes of severe eosinophilic asthmatics' fibroblasts can contribute to airway remodelling, at least in part, by modulating epithelial cell proliferation observed in severe asthma.